Upaya Perlindungan Hukum Bagi Pegawai Pemerintahan Dengan Perjanjian Kerja Dalam Pemutusan Hubungan Kerja - Yemima Andria Hotmauli Simanjuntak (Jurnal Syntax Transformation, 2022)
Efforts to realize the reform of the government bureaucracy that prioritizes transparency, accountability, efficiency, effectiveness, productivity to eradicate corruption, the government seeks to eradicate the bad stigma from the wider community towards the image of civil servants. As contained in Law Number 5 of 2014 (ASN Law), the classification of State Civil Apparatus (ASN) consists of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). The ASN Law with its derivative rules, namely Government Regulation (PP) Number 49 of 2018 concerning Management of Government Employees with Work Agreements has not been able to provide legal certainty for PPPK because it actually creates large gaps such as the gap in rights between PPPK and PNS, especially in the right to terminate relations. work. Therefore, in this study, we will examine the legal protection efforts for PPPK in terminating employment based on the ASN Law and examine legal remedies that can be taken by PPPK in the event of an instant termination of employment. To deal with matters relating to Termination of Employment Contracts (PHPK) currently, administrative measures can be used, which consist of objections and appeals in resolving employment disputes, especially for PPPK. The results of this study used a normative juridical approach which was carried out based on the main legal material. The purpose of this research is to find out the appropriate legal protection for PPPK related to the termination of the employment agreement based on Law Number 5 of 2014 and legal remedies that can be taken. Suggestions from the results of this study are legislators can formulate implementing regulations both in the form of perfecting regulatory loopholes related to reasons for respectful dismissal not at their own request and regulatory loopholes in legal remedies for PHPK.